Indonesian Learners' Requests in English: A Speech-Act Based Study - F.X. Nadar (Faculty of Cultural Sciences, Universitas Gadjah Mada, 1998)
This paper investigates requests by Indonesian learners based on speech act theories. It attempts to find the charaderistics of the requests, and discuss the findings from the view points of forms and politeness strategy. This essay consists of five main parts. They are the introduction, brief theoretical aspects of making requests, methodology, result and discussion and conclusion. Language is a means of communication, and people use language for various reasons, Finegan, et al.(1992:3) state that language has been viewed as a vehicle of thought, a system of expression that mediates the transfer of thought from one person to another. They also claim (p.305) that